Description of three females of the genus Acanthagrion (Odonata: Coenagrionidae) with a key to the females of Argentina - Lozano, Federico (Zootaxa, 2013)
The neotropical genus Acanthagrion Selys (Odonata: Coenagrionidae) is composed of 44 species, of which the females of 31 species are currently known. In this contribution the females of A. aepiolum Tennessen and A. minutum Leonard are described and that of A. ascendens Calvert is redescribed. Distribution maps and new records are provided for all three species. Finally, a key to females of the genus Acanthagrion from Argentina is provided.